Akselerasi Human Resource Scorecard: Kontribusi Komitmen Organisasi dan Gaya Kepemimpinan dengan Budaya Organisasi Sebagai Katalis - Desi Qurani Kholid; Nuraeni Nuraeni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of Organizational Culture and Leadership Style on the Human Resource Scorecard (HRS) through Organizational Culture among employees of PT SMRA, particularly in the Education unit. The study examines the role of Organizational Culture as a mediating variable in the relationship between Organizational Commitment, Leadership Style, and the Human Resource Scorecard. A descriptive and explanatory research design with a quantitative approach was employed. Data were collected through questionnaires distributed to 92 employees and analyzed using SmartPLS with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results indicate that the Human Resource Scorecard is directly influenced by Organizational Commitment, Leadership Style, and Organizational Culture. Furthermore, Organizational Culture is proven to fully mediate the effects of organizational commitment and leadership style on HRS. These findings emphasize the synergy between employee commitment, leadership style, and organizational culture, which must be strengthened to generate a significant impact on the achievement of HRS. Improving HRS also plays a crucial role in sustaining organizational success. Therefore, regular evaluation of Human Resource Scorecard performance is necessary to ensure that human resource policies and practices remain aligned with the company’s strategic objectives.